Assessment of the Perception of Security Based on CPTED in Bundaran HI TOD - Siti Nurlaela; Sugiono Sugiono; Nadhila Alda Ismiralda; Ardy Maulidy Navastara; Ema Umilia; Arwi Yudhi Koswara (Diponegoro University, 2021)
CPTED studies has been popular since 1960-1970s, however studies in Indonesian city context showed limited references. This paper identified the need of CPTED study followed a massive MRT network development in Jakarta City, as the need for re-design and city beautification to fit with the vibrant TOD urban lifestyle may create moments as well to promote CPTED implementation. The perception survey was developed to understand the perceived crime risk level among the MRT users of Bundaran HI Station. The survey conducted in two scopes of context, i.e. the TOD precinct, an area of 800 radius from the station, and inside the station itself. Finding from the TOD context showed that the maintenance and information have been the most significant but often mostly ignored. These two component may lead to under-rated other CPTED components, weaken the territorial reinforcement and natural surveillance. Out of 56 parameters, 26 parameters or almost halve have rated below 3, alarmed for a more comprehensive design and intervention at the TOD neighbourhood level that emphasizes on the implementation of CPTED principles. Finding from the Bundarin HI station context showed that under the Likert scale 1 (the lowest risk) to 5 (the highest risk), most of the CPTED rated from 4 – 5. There were a variation in the perceived security among different respondents based on gender, time pattern, location pattern, and mode chosen for station access. However, these rating differences were not significant according to the ANOVA and the t-test statistics. The chi-square test found no association between the perceived securities with the type of mode uses for station access. These preliminary findings suggested that the Bundaran HI TOD station is secured from crime risk according to perception of MRT users; therefore little variation in the rating of perceived security gave little information to draw any association with other important variables such as the mode choice for station access. However, taken the measures on wider context at the TOD precinct, the rating of CPTED consistently lower in all components, suggested the urban design and land use zoning-and transportation intervention that consider CPTED principles to be emphasizing at wider area to support the security of the station.